3D modeling with the ThreeJS Framework of the Colonial Temple of Chuquinga Aymaraes – Perú - Pimentel Palomino, Michael Alexander (2019)
This research has the purpose of modeling in 3D of the Colonial Temple of Chuquinga, to prove the rendering time in mobile devices, the investigation is applied, with an explanatory level and an experimental design where the rendering time with the frequency was evaluated of images (FPS, obtaining the frequency of images (FPS), the average is 52.29 FPS, highlighting the most influential GPU, that is, increases the frequency of images (FPS) when the central clock is greater than 500 Mhz in all mobile devices that have an optimum level, while in basic level devices when GPM Mhz decreases, the frequency of images (FPS) decreases, however, it does not cause distortion in animations and textures. The ThreeJS library was used to create 3D objects, 3ds Max for the modeling of temple walls and WebGL for final rendering